The Comprehensive study of Multilevel Inverter - A.Ambikapathy, Chandan Kumar, Rahul Kumar, Pravek Singh, Sadan, Himanshu (International Journal of Advanced Science and Technology, 2020)
This paper well describe the concept of multilevel inverter. Multilevel inverter is an emerging technology for basically industrial purpose to convert dc to an ac supply ,in it no. of DC source is used as an input through it total harmonic distortion of supply is reduced . The multilevel inverter output approaches more sinusoidal for voltage and current. According to circuit diagram multilevel-inverter has various types like diode clamp ,flying capacitor and h- bridge multilevel inverter. The inverter circuit works on pulse width modulation technique. Keywords: THD (Total harmonic distortion),MLI (Multilevel-inverter),FCMLI(Flying capacitor multilevel -inverter)